Finite size scaling study of lattice models in the three-dimensional Ising universality class - Hasenbusch, Martin (Physical review. B, Condensed matter and materials physics, 2010)
We study the spin-1/2 Ising model and the Blume-Capel model at various values of the parameter D on the simple cubic lattice. To this end we perform Monte Carlo simulations using a hybrid of the local Metropolis, the single cluster and the wall cluster algorithm. Using finite size scaling we determine the value D∗=0.656(20) of the parameter D, where leading corrections to scaling vanish. We find ω=0.832(6) for the exponent of leading corrections to scaling. In order to compute accurate estimates of critical exponents, we construct improved observables that have a small amplitude of the leading correction for any model. Analyzing data obtained for D=0.641 and 0.655 on lattices of a linear size up to L=360 we obtain ν=0.63002(10) and η=0.03627(10). We compare our results with those obtained from previous Monte Carlo simulations and high-temperature series expansions of lattice models, by using field-theoretic methods and experiments.
Gesehen am 09.09.2022